Highly Efficient Methylene Blue Dye Removal by Nickel Molybdate Nanosorbent - Souad Rakass; Hicham Oudghiri Hassani; Ahmed Mohmoud; Fethi Kooli; Mostafa Abboudi; Eman Assirey; Fahd Al Wadaani (Molecules, 2021)
Removing methylene blue (MB) dye from aqueous solutions was examined by the use of nickel molybdate (α-NiMoO4) as an adsorbent produced by an uncomplicated, rapid, and cost-effective method. Different results were produced by varying different parameters such as the pH, the adsorbent dose, the temperature, the contact time, and the initial dye concentration. Adsorbent dose and pH had a major removal effect on MB. Interestingly, a lower amount of adsorbent dose caused greater MB removal. The amount of removal gained was efficient and reached a 99% level with an initial methylene blue solution concentration of ≤160 ppm at pH 11. The kinetic studies indicated that the pseudo-second-order kinetic model relates very well with that of the obtained experimental results. The thermodynamic studies showed that removing the MB dye was favorable, spontaneous, and endothermic. Impressively, the highest quantity of removal amount of MB dye was 16,863 mg/g, as shown by the Langmuir model. The thermal regeneration tests revealed that the efficiency of removing MB (11,608 mg/g) was retained following three continuous rounds of recycled adsorbents. Adsorption of MB onto α-NiMoO4 nanoparticles and its regeneration were confirmed by Fourier transform infrared spectroscopy (FTIR) analysis and scanning electron microscopy (SEM) analysis. The results indicated that α-NiMoO4 nanosorbent is an outstanding and strong candidate that can be used for removing the maximum capacity of MB dye in wastewater.